Changes In Planning and Controlling Competencies After Management-Based Leadership Training: A Single-Group Pre-Test And Post-Test Study Among Manufacturing Supervisors - Kristian Dwi Kusuma; Djudiyah (Jurnal Ilmu Pendidikan dan Sosial, 2026)
Leadership effectiveness is a critical factor in supporting organizational performance, yet many supervisors and managers continue to experience limitations in managerial competencies, particularly in planning and controlling. This study aimed to examine the effectiveness of management-based leadership training in improving leadership competencies through strengthening these two managerial functions. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design involving 37 manufacturing industry employees selected through purposive sampling. The intervention consisted of an eight-hour face-to-face management-based leadership training integrating experiential learning methods, including lectures, case discussions, simulations, reflective activities, and structured feedback. Data were collected using leadership competency tests administered before and after the training and analyzed using descriptive statistics, the Shapiro–Wilk normality test, paired-samples t-test, and Cohen's dz effect size. The findings revealed that the mean competency score increased from 58.38 (SD = 14.24) in the pretest to 75.95 (SD = 12.35) in the posttest. The paired-samples t-test indicated a statistically significant improvement, t(36) = −6.091, p < .001, with a large effect size (Cohen's dz = 1.001), demonstrating that the intervention substantially enhanced participants' planning and controlling competencies. These findings suggest that management-based leadership training is an effective approach for strengthening managerial leadership competencies and provide practical evidence for designing competency-based leadership development programs within organizational settings.